External Security Guarantees and Their Impact on Civil War Termination - Harvey, Craig (Cranfield University, 2020)
Civil wars are notoriously difficult to terminate, with commitment problems increasingly seen as the primary cause for this failure. This research investigates the role that security guarantees and peace enforcement plays in overcoming these difficulties. It utilises linear regressions on a dataset including every civil war initiated between 1940 and 2007, and Cox Proportional Hazard models on a second dataset including every peace agreement between 1976 and 2008 along with case studies of Kosovo, Cote d'Ivoire and Liberia. Furthermore, it uses three different definitions, two of which drawn from the existing literature, to assess the impact of security guarantees. The results of the regressions show that a promise of a security guarantee is not as effective as a deployment of forces with a mandate to intervene and actively guarantee the existence of belligerents, and that where a leader is refusing to give up power, peace enforcement can be beneficial.
Keywords: 'DSDS20 3MT'; 'DSDS20'; 'Civil War'; 'Commitment Problems'; 'Conflict Termination'; 'Defence Studies'